Peran Kepemimpinan Sekolah dalam Meningkatkan Kinerja Guru dan Budaya Sekolah pada Pembelajaran IPS : Sebuah Kajian Sistematis - Makrus Makrus; Istichomahwati Istichomahwati; Riyanto Dwi Utomo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the role of elementary school principal leadership in improving teacher performance and forming a positive school culture. The method used is the Narrative Literature Review (NLR), by analyzing seven relevant articles from 2019–2025. The results of the study indicate that effective leadership, both in transformational and participatory forms, plays an important role in motivating teachers, providing quality supervision, and creating a harmonious work environment. In addition, principals who have good communication and conflict management skills are able to build a school culture that supports character development and student achievement. These findings indicate the need to strengthen the leadership competencies of principals to create a productive work climate and support the improvement of the quality of elementary education as a whole.